Renovación curricular: una vía para la reflexión de la calidad educativa en Colombia: Curricular renewal: a way for reflection on educational quality in Colombia - Cardozo Cruz, Jonatan; Mejía Guarín, Sandra; Álvarez Giraldo, Neidy (Encuentro Educacional, 2024)
In recent decades, various educational reforms have been introduced, focused on responding to the demands of a globalized world and improving educational quality, and Colombia is no exception. This research aimed to critically analyze the different educational reforms and curricular renovations that have been carried out in Colombia and their impact on educational quality. Documents published by the Ministry of National Education are analyzed (MEN, 1996; MEN 2007; MEN 2017). A qualitative approach was applied, with a documentary review, characterizing the information with the help of hermeneutics to assimilate, elucidate and ponder regarding the selected topic from the different bibliographic sources explored. It is observed that some Ten-Year National Education Plans made significant contributions, although their execution was incipient in some cases. In Colombia, the State is the mediator in the creation of laws and decrees, thus curricular renovation stands out as a crucial point to improve educational quality. One of the most representative deductions in this research is the need to promote educational and curricular policies that support the reconstruction of the Colombian educational system and its subsequent reconfiguration with the help of dialogic and critical curricular renewal, which results in the transformation of social and cultural reality.